The Fanconi Anemia Core Complex Is Dispensable during Somatic Hypermutation and Class Switch Recombination - Krijger, Peter H. L.; Wit, Niek; van den Berk, Paul C. M.; Jacobs, Heinz (PloS one, 2010)
To generate high affinity antibodies during an immune response, B cells undergo somatic hypermutation (SHM) of their immunoglobulin genes. Error-prone translesion synthesis (TLS) DNA polymerases have been reported to be responsible for all mutations at template A/T and at least a fraction of G/C transversions. In contrast to A/T mutations which depend on PCNA ubiquitination, it remains unclear how G/C transversions are regulated during SHM. Several lines of evidence indicate a mechanistic link between the Fanconi Anemia (FA) pathway and TLS. To investigate the contribution of the FA pathway in SHM we analyzed FancG-deficient B cells. B cells deficient for FancG, an essential member of the FA core complex, were hypersensitive to treatment with cross-linking agents. However, the frequencies and nucleotide exchange spectra of SHM remained comparable between wild-type and FancG-deficient B cells. These data indicate that the FA pathway is not involved in regulating the outcome of SHM in mammals. In addition, the FA pathway appears dispensable for class switch recombination.